Geo-Forensic Criminal Law: Strengthening Environmental Criminal Evidence in the Mining Sector Through Geospatial Technology - Ayu Putriyana; Zico Junius Fernando; Wevy Efticha Sary; Mardhatillah (Universitas Sriwijaya, 2026)
The expansion of mining investments within the framework of national economic development is often accompanied by an increased risk of environmental damage that is difficult to prove through conventional means, especially in remote areas with complex licensing. This condition raises the issue of the effectiveness of evidence in environmental criminal law enforcement, considering that ecological crimes often occur covertly and require precise scientific analysis. This study examines the main problem of how geospatial technologies such as high-resolution satellite imagery, GIS-based mapping, LiDAR, and drone monitoring can serve as geo-forensic instruments to strengthen criminal evidence in mining cases. Using a normative research method, this study analyses the evidentiary regulatory framework in the 2009 Environmental Protection and Management Law (UU PPLH) and the scientific evidentiary standards in judicial practice. It juxtaposes them with actual case studies of mining crimes in Indonesia. The results of the study indicate that geospatial evidence has strong evidentiary value because it can present digital traces of environmental damage in real time and with traceability; however, there are still normative challenges related to data authentication, the digital chain of custody, and the capacity of law enforcement officials. This research concludes that there is a need to construct a Geo-Forensic Criminal Law as a modern evidentiary framework that integrates geospatial science into the environmental criminal evidence system to improve accuracy, effectiveness, and legal certainty in the supervision of the mining industry